Implementasi Penilaian Afektif Pada Mata Pelajaran PAI - Thomas Agusta; Wirdati Wirdati (An-Nuha, 2022)
This article aims to describe the implementation of affective assessment on PAI subjects in schools, especially at the junior high school level, with qualitative methods on a case study approach, data collection methods using observation and interview methods, data sources taken from informants through interviews, consisting of (representatives) head of curriculum, PAI teachers, and students) who were selected using purposive sampling, a sampling approach in which the researcher is based on his own judgment when selecting contributors from the population to participate in his research. For the validity of the data by using source triangulation techniques. In strengthening the interview, the author made observations using direct mastery techniques in the classroom. All interview information and statements were then analyzed thematically using descriptive methods. Overall, the study found 4 implementations of affective assessment in PAI subjects. The four forms of affective assessment are: i) assessment through observation is done by seeing students in action at school, PAI teachers have difficulty in assessing observations because face-to-face learning is divided per shift, PAI teachers have not been able to monitor students 100%, ii ) self-assessment is carried out by the teacher when students ask questions during learning hours, iii) assessment between friends through positive assessments of one student with another student, iv) attitude assessment journal by the PAI teacher by looking at students in class then the results of the assessment are carried out on student reports.